2009
DOI: 10.1002/ps.1706
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of natural and synthetic signalling molecules in parasitic weed germination

Abstract: The structures of naturally occurring germination stimulants for seeds of the parasitic weeds Striga spp. and Orobanche spp. are described. The bioactiphore in this strigolactone family of stimulants is deduced from a structure-activity relationship and shown to reside in the CD part of the stimulant molecule. A molecular mechanism for the initial stages of seed germination is proposed. The influence of stereochemistry on the stimulant activity is significant. Combining this molecular information leads to a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
209
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(212 citation statements)
references
References 99 publications
2
209
1
Order By: Relevance
“…or Orobanche spp. population (Zwanenburg et al 2009). Furthermore, root volatiles might also have positive effects on neighboring plants.…”
Section: Plant-plant Interactionmentioning
confidence: 99%
“…or Orobanche spp. population (Zwanenburg et al 2009). Furthermore, root volatiles might also have positive effects on neighboring plants.…”
Section: Plant-plant Interactionmentioning
confidence: 99%
“…1A). It has been reported that this enol ether bridge is not only essential for parasitic seed germination, 12,13 but is also required for the induction of AM branching 14 and their hormonal activity in planta. 15 Although the main structure of strigolactones is rather similar, their A-and B-ring decoration and stereochemistry can vary substantially (Fig.…”
mentioning
confidence: 99%
“…A number of publications have discussed their implementation as inducers of suicidal seed germination of parasitic plant (Zwanenburg et al, 2009(Zwanenburg et al, , 2013Vurro and Yoneyama, 2012). However, strigolactones may be used in additional approaches for the development of new agricultural methodologies and technologies compatible with emerging concepts of sustainable agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…Strigolactone inhibitors may be used to enhance rooting of plant cuttings (Rasmussen et al, 2012), potentially promoting the propagation of woody plants for the industry and conservation of endangered species. Today's new strigolactone analogs and mimics, which are under development or being synthesized (Zwanenburg et al, 2009;Prandi et al, 2011), are likely to substantially promote the ability to use strigolactones to the benefit of agriculture. Received June 9, 2014;accepted July 14, 2014;published July 18, 2014. LITERATURE CITED…”
Section: Discussionmentioning
confidence: 99%